2009
DOI: 10.1158/0008-5472.sabcs-09-1008
|View full text |Cite
|
Sign up to set email alerts
|

SENTinel Node Biopsy before or after NeoAdjuvant Systemic Treatment – The German SENTINA Trial.

Abstract: Background: For patients with breast cancer undergoing neoadjuvant systemic treatment (NST) the optimal timing of sentinel node biopsy (SLNB) is unclear. While adequate axillary staging prior to NST could allow for a-priori tailoring of systemic treatment, SLNB after NST could spare those patients from complete axillary dissection (AD), who are free of metastases in the axilla or convert from a positive (Npos) to a negative (Nneg) axillary status following NST. For these patients, however, the reliability of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…There is a current SNB trial looking at SNB before and after neoadjuvant systemic therapy in Germany called SENTINA (Kuehn et al, 2009). This is a four arm study.…”
Section: Role Of Sentinel Node Biopsy After Neoadjuvant Systemic Therapymentioning
confidence: 99%
“…There is a current SNB trial looking at SNB before and after neoadjuvant systemic therapy in Germany called SENTINA (Kuehn et al, 2009). This is a four arm study.…”
Section: Role Of Sentinel Node Biopsy After Neoadjuvant Systemic Therapymentioning
confidence: 99%
“…The landmark Sentinel Neoadjuvant (SENTINA) study and the American College of Surgeons Oncology Group (ACOSOG) Z1071 trial evaluated the accuracy of post-NST SLNB in cN+ disease and found false-negative rates (FNRs) of 14.6% and 12.6%, respectively, raising questions about the safety of SLNB in this population. 1,2 In the ACOSOG Z1071 trial, dual-agent mapping and excision of the clipped node reduced the FNR to 10.8% and 6.8%, respectively. 3 Caudle et al 4 formalized the practice of targeted axillary dissection (TAD), which includes removal of the clipped node with SLNB and demonstrated an FNR of 2%.…”
mentioning
confidence: 99%